Tundra cryogenic land surface processes and CO2–C balance in sub-Arctic alpine environment withstand winter and spring warming - Väisänen, Maria; Klaminder, Jonatan; Ylänne, Henni; Teuber, Laurenz; Dorrepaal, Ellen; Krab, Eveline J (Environmental Research: Climate, 2023)
Cryogenic land surface processes (CLSPs), such as cryoturbation, are currently active in landscapes covering 25% of our planet where they dictate key functions, such as carbon (C) cycling, and maintain patterned landscape features. While CLSPs are expected to diminish in the near future due to milder winters especially in the southern parts of the Arctic, the shifts in C cycling in these landscapes may be more complex, since climate change can affect C cycling directly but also indirectly via CLSPs. Here, we study the effects of changing winter and spring climate on CLSPs and C cycling in non-sorted circles consisting of barren frost boils and their vegetated rims. We do this by measuring cryoturbation and ecosystem CO2 fluxes repeatedly in alpine subarctic tundra where temperatures during naturally snow covered period have been experimentally increased with snow-trapping fences and temperatures during winter and spring period after snowmelt have been increased with insulating fleeces. Opposite to our hypothesis, warming treatments did not decrease cryoturbation. However, winter warming via deeper snow increased ecosystem C sink during summer by decreasing ecosystem CO2 release in the frost boils and by counterbalancing the negative effects of cryoturbation on plant CO2 uptake in the vegetated rims. Our results suggest that short-term changes in winter and spring climate may not alter cryoturbation and jeopardize the tundra C sink.